Population of brown planthopper (Nilaparvata lugens) in paddy field at Kampung Dahlia Bachok, Kelantan / Siti Musliha Ismail - Ismail, Siti Musliha (Faculty of Plantation and Agrotechnology, 2016)
The brown plant hopper (BPH) is a serious rice pest in Asia and one of the insect that gives the damage to the crop protection and can reduce the production at every year. The Small outbreaks were reported in Malaysia, such as in Malacca in 1939. The insects are assault on the surface of leave and cause the hopper bum. This study was design to know the population of Brown Planthopper (Nilaparvata lugens) at Kampung Dahlia Bachok, Kelantan by using yellow pan trap method. Yellow pan trap is the simple trap but effective to trap the BPH because most of insect like a bright color. The SPSS result also show that the data of BPH is not normally distributed (p< 0.05) According to the Kruskal- wallis test shows that the BPH was significant among different time of collection.